Safety of Prone Jackknife Position in Ambulatory Anorectal Surgery - Fareed Cheema; Sabair Lee; Marcus Zebrower; Juan Lucas Poggio (World Journal of Colorectal Surgery)
Background and Objectives: The objectives of this study were to determine morbidity and mortality rates of ambulatory anorectal surgeries in prone jackknife position. Patients and Methods: Retrospective chart analysis on 210 patients undergoing ambulatory anorectal surgery in the prone jackknife position. The primary endpoint studied was mortality and complication rates. Other factors analyzed were age, sex, clinical diagnosis, procedure, past medical history, American Society of Anesthesiologists physical status classification, current smoking status, mean pre- and post-operative mean arterial pressure (MAP), mean minimum intraoperative MAP, minimum intraoperative O2saturation, estimated blood loss, fluids given, anesthesia duration, antibiotic administration, and days to discharge and whether there were any readmissions within 30 days. To assess significant differences between pre-, intra-, and post-operative mean arterial pressure, one-way ANOVA was used. Results: There was no mortality within 30 days of surgery. Complication rate was 3.3% with urinary retention being the most common, comprising 42% of all complications. Thirty-day readmission rate from surgery was 1%. Mean pre- and post-operative MAP was 88.4 ± 11.4 and 90.6 ± 11.9, respectively. Mean minimum intraoperative MAP and O2saturation was 70.6 ± 9.5 and 98.7% ± 1.6%, respectively. Mean minimum intraoperative MAP was significantly decreased compared to mean pre- and post-operative MAP (P < 0.05). Conclusion: Prone jackknife position supports the chest while relaxing the abdomen by flexing at the hips. In ambulatory anorectal surgeries under general anesthesia, given the hemodynamic stability and lack of intra- and post-operative complications, prone jackknife position is a noninferior alternative to supine or lithotomy position.